Forecasting models for national economic planning - Heesterman, A. R. G. (Dordrecht : Reidel, 1970)
This book is about specification of linear model and parameter-estimation.
Includes bibliographical references: p. 129-132.
oo 14/09/2018
Loans
Keywords: Economic policy; Economic forecasting